Bioaugmentation of atrazine removal in constructed wetland: Performance, microbial dynamics, and environmental impacts. (October 2019) - Zhao, Xinyue; Bai, Shunwen; Li, Chunyan; Yang, Jixian; Ma, Fang
Graphical abstract: Highlights: Feasibility test of enhanced atrazine-removal in constructed wetland using bioaugmentation. Inoculating functional bacteria markedly increased the atrazine degradation. Inoculated bacteria indicated high adaptability and degradation contribution. Benchmarking the marginal environmental burdens of enhancing one kg atrazine removal. Bioaugmented CW showed shorter payback period than non-bioaugmented CW. Abstract: Constructed wetland (CW) is an efficient technology to treat urban storm water runoff. However, the CW has limited capacity to degrade atrazine, a frequently detected herbicide in runoff. Bioaugmentation provides a feasible enhanced alternative; nevertheless, incorporating bioaugmentation into CW is likely to perpetuate the environmental consequences and incur complex trade-offs between environmental improvement and burdens. Since few efforts were made to improve above situation, the present work proposed the application of bioaugmentation, and tested the feasibility from both efficiency and sustainability dimensions. Results showed that bioaugmentation markedly enhanced atrazine degradation from 5 mg/L to below the threshold value within 43 day by increasing functional atrazine-degrading bacteria. Pseudomonas and Arthrobacter significantly proliferated among atrazine-degrading bacterial genera, indicating high adaptability and atrazine-degrading contribution. With life cycle assessment, enhancing 1 kg of atrazine degradation could decrease environmental burdens with 27.60 kg 1, 4-DCB-Eq of freshwater-ecotoxicity reduction, and achieve shorter payback period compared to non-bioaugmented CW.